2011
DOI: 10.1007/s10646-011-0670-9
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of crude extracts of cyanobacteria from Taihu Lake on carp (Cyprinus carpio)

Abstract: Genotoxicity of crude cyanobacteria extracts (CBE) from blooms in Taihu Lake, China toward common carp (Cyprinus carpio) was measured. The primary extracellular product was determined by HPLC to be Microcystin-LR (MC-LR, L for leucine and R for arginine) with an average concentration of 2.4 × 10(2) μg MC g(-1) dry weight of cyanobacteria. Acute toxicity to carp, expressed as the 72-h LC(50,) was 53 mg, dw cyanobacteria L(-1). Genotoxicity, as determined by the micronucleus (MN) and comet assays were both dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Similarly, MN numbers were increased by in vivo treatment with ZEN in all feeding groups in the present study ( Table 4 ). Although the percentage of MN was higher than observed in carp erythrocytes after microcystin treatment [ 67 ], it was comparable to the levels observed in ZEN-treated mice [ 15 ]. This is in line with the increasing concern about possible carcinogenic actions of ZEN in vertebrates [ 46 , 68 ], and may be problematic for fish in aquaculture since the ZEN concentrations used in the experimental diets in this study were far below the maximum allowable levels in complete feedstuffs recommended by the European Commission [ 41 ].…”
Section: Resultssupporting
confidence: 57%
“…Similarly, MN numbers were increased by in vivo treatment with ZEN in all feeding groups in the present study ( Table 4 ). Although the percentage of MN was higher than observed in carp erythrocytes after microcystin treatment [ 67 ], it was comparable to the levels observed in ZEN-treated mice [ 15 ]. This is in line with the increasing concern about possible carcinogenic actions of ZEN in vertebrates [ 46 , 68 ], and may be problematic for fish in aquaculture since the ZEN concentrations used in the experimental diets in this study were far below the maximum allowable levels in complete feedstuffs recommended by the European Commission [ 41 ].…”
Section: Resultssupporting
confidence: 57%
“…Recently, Wu et al [20] has found that a cyanobacterial extract containing MC-LR was able to induce DNA and chromosome damage detected by the micronucleus assay and the SCGE assay in carp erythrocytes and kidney cells after a few-day in vivo exposure. Proapoptotic and cytotoxic influence of MC-LR on carp leukocytes, manifested as the increase of LDH leakage, increased number of apoptotic and necrotic cells, changes in intracellular GSH levels and affected phagocytic activity, was also observed by Rymuszka [21].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on the potential genotoxicity of cyanobacterial products on these organisms. Available data indicate that cyanotoxins may induce changes in nuclei of kidney cells, erythrocytes or embryos of different fish species [18][19][20]. Moreover, disruption of some vital functions of immune cells of fish was reported [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the biochemical characterization of organophosphonate biodegradation processes by cyanobacteria is still scarce and incomplete. On the other hand, it has been shown that many enzymes in cell‐free extracts from cyanobacterial cultures, although unrelated to phosphonate metabolization, retain their activity following freezing or lyophilization (Sanevas et al ., ; Hao et al ., ; Osswald et al ., ; Wu et al ., ).…”
Section: Introductionmentioning
confidence: 97%